Commercialization of Roads : A New Generation of Road Funds - World Bank (Washington, DC, 2012)
The objective of this paper is to address the issue of building institutional and financial capacity for maintenance of the road network. Lessons learned: the involvement of road users and other stakeholders in the management of funds wins public support and strengthens market discipline; and the introduction of sound business practices in the operations of road funds provides incentives for more efficient management.